Nursing Activities for Patients With Chronic Disease in Primary Care Settings: A Practice Analysis. Issue 1 (January 2018) - Poitras, Marie-Eve; Chouinard, Maud-Christine; Gallagher, Frances; Fortin, Martin
Abstract : Background: Nurses in primary care organizations play a central role for patients with chronic disease. Lack of clarity in role description may be associated with underutilization of nurse competencies that could benefit the growing population of patients with chronic disease. Objective: The purpose of the research was to describe nursing activities in primary care settings with patients with chronic disease. Methods: A Web-based survey was sent to nurses practicing in Family Medicine Groups in the Canadian Province of Québec. Participants rated the frequency with which they carried out nursing activities in five domains: (a) global assessment, (b) care and case management, (c) health promotion, (d) nurse–physician collaboration, and (e) planning services for patients with chronic disease. Findings were summarized with descriptive statistics (means, standard deviations, and ranges). Results: The survey was completed by 266 of the 322 nurses who received the survey (82.6%). Activities in the health promotion and global assessment of the patient domains were carried out most frequently. Planning services for patients with chronic disease were least frequently performed. Discussion: This study provides a broad description of nursing activities with patients with chronic disease in primary care. The findings provide a baseline for clinicians and researchers to document and improve nursing activities for optimal practice for patients with chronic disease.